Why Should I Help You? Man Up! Bystanders' Gender Stereotypic Perceptions of a Cyberbullying Incident. Issue 5 (4th May 2019) - Weber, Mathias; Koehler, Christina; Schnauber-Stockmann, Anna
ABSTRACT: Bystanders observing a cyberbullying incident do not always intervene in favor of the victim. We argue that gender stereotypic perceptions of female versus male victims contribute to the differential reactions of bystanders to cyberbullying incidents. Results of a scenario-based experiment show that participants with moderate or high levels of sexist attitudes are more empathic toward a female victim of workplace cyberbullying. Consequently, a female victim is more likely to receive help. Female victims are less likely to be attributed blame if the perpetrator is male. The results imply that male victims of cyberbullying are marginalized by their social environment.